Financial Literacy among the Millennial Generation: Relationships between Knowledge, Skills, Attitude, and Behavior - Vera Dewi; Erie Febrian; Nury Effendi; Mokhamad Anwar (Australasian Accounting, Business and Finance Journal, 2020)
This study aims to determine the level of financial literacy among the millennial generation and to examine the correlation of their financial knowledge, financial attitude, and financial skills with their financial behavior. Multiple choice questions were used to measure financial knowledge with results grouped into three categories: low, moderate, and high. Financial attitude, financial skills, and financial behavior were also grouped using the quartile method into three categories: poor, fair, and good. Chi-squared analysis was used to test the hypotheses, with correspondence analysis conducted to identify the characteristics of the millennial generation and to graphically illustrate the gap. Regarding financial attitude, financial skills, and financial behavior, the proportions of respondents in the 'fair' category, were 70.6%, 66.5%, and 72.2%, respectively. Significant relationships were found not only between financial attitude and financial management behavior, but also between financial skills and financial management behavior. However, the relationship was not significant between financial knowledge and financial behavior.
Keywords: Financial attitude; Financial behavior; Financial knowledge; Financial literacy; Financial skills